Pengaruh Kualitas Produk, Citra Merek, Dan Harga Terhadap Loyalitas Konsumen (Studi Pada Konsumen Citra Kendedes Cake & Bakery) - Evita Maifani; Budi Wahono; Nanik Wahyuningtyas (UNIVERSITAS ISLAM MALANG, 2023)
Abstract Seeing the high potential value of the development of the Cake & Bakery Industry, of course this will have an impact on high demand and the emergence of new players from this industry. One such company is Citra Kendedes cake & bakery Malang. The purpose of research with this type of explanatory research and quantitative approach is to find out and analyze product quality, brand image, and price on consumer loyalty, either simultaneously or partially. The sampling technique used was a purposive sampling technique, in which the sample selected was the respondent who purchased the product at the store more than once and also consumed the bakery product. Determining the number of samples using the Malhotra formula which then found a number of 100 respondents. This research method uses multiple linear regression analysis with the SPSS analysis tool. Based on the results of this study product quality, brand image, and price simultaneously and partially have an influence on consumer loyalty. Keywords : Product Quality, Brand Image, Price, and Consumer Loyalty